Quality Assessment Across Disciplines in Head and Neck Cancer Treatment Diagnostic Pathology in HNSCC - Sloan, Philip; Robinson, Max (Frontiers in Oncology, 2020)
Quality assured pathology services are integral to provision of optimal management for patients with head and neck cancer. Pathology services vary globally and are dependent on resources in terms of both laboratory provision and availability of a highly trained and accredited workforce. Ensuring a high-quality pathology service depends largely on close working and effective communication between the clinical team providing treatment and the pathologists providing laboratory input. Laboratory services should be quality assured by achieving external accreditation, most often by conforming to International Organization for Standardization (ISO) standards such as ISO15189 sometimes with ISO17025 or alternatively ISO17020. Quality of diagnostic reporting can be assured by the ISO but clinical teams should endeavor to work with pathologists who engage in continuing professional development, external quality assurance and audit. Research also contributes to diagnostic reporting quality. A number of initiatives in the UK such as the EPSRC/MRC funded Molecular Pathology Nodes and the National Cancer Research Institute Cellular-Molecular Pathology initiative (C-M Path), for example, have linked pathologists, industry and researchers. This has resulted in centers leading in digital innovation, artificial intelligence, translational research and clinical trials supported by pathologists. For rare tumors and contemporary molecular diagnostics, biopsy material can increasingly be shared with expert specialist pathologists working in specialist centers, particularly by using digital pathology platforms with potentially global reach. High quality services for the majority of diagnostic processes required for head and neck cancer management is best provided by local pathologists where communication with the treating team is more effective than with pathologists working in remote centers. Quality assurance is an increasingly important aspect of pathology, assuring not only effective turnaround times and accuracy for the diagnostic service but also high quality consistent reporting for clinical trials where even small pathology errors can potentially produce a significant bias and in the worst case negate the value of a completed trial. Better outcomes have been associated with centers engaged in clinical trials than in non-participating centers. Provision of a quality assured pathology service should extend to both the research and diagnostic services.